Survival of Pancreatic Cancer Patients in Dr Cipto Mangunkusumo National Referral Hospital Jakarta from November 2018 To December 2018 - Kaka Renaldi; Atikah Isna Fatya; Sharifah Sakinah (The Indonesian Society for Digestive Endoscopy, 2019)
Background: Pancreatic cancer is a leading cause for cancer deaths worldwide and its survival rate remains low. The one year- and five year-survival rate remain as low as 21% and 6-8% consecutively. Little is known about the survival rate of pancreatic cancer in Indonesia. This study aims to evaluate the survival rate of pancreatic cancer patients at Gastrointestinal Endoscopy Center, National Referral Hospital Dr. Cipto Mangunkusumo, Jakarta, during November 2018 to December 2018.Method: This retrospective cohort study extracted the registry data of newly diagnosed pancreatic cancer patients between November 2018 to December 2018 from the Gastrointestinal Endoscopy Center, Cipto Mangunkusumo Hospital, Jakarta. All patients were followed since they were diagnosed to two months after diagnosis or 31st December 2018 or to their date of death, whichever came first.Results: We found 12 newly diagnosed pancreatic cancer cases between November 2018 to December 2018. The mean age at diagnosis was 55 years old, with 58% male, 50% sundanese, and 75% patient come from low educated level. About 58% cases presented with cholangitis, and the mean bilirubin concentration at diagnosis was 26 mg/dL. All patient came with an obstructive jaundice symptoms, and 91% had endoscopic biliary drainage procedure. After 2 months of observation, we found 16% patient died due to unresolved infection.Conclusion: There were 12 cases of pancreatic cancer, of which 16% pancreatic cancer patients died within 2 months of follow up. Infection is the main cause of morbidity and mortality in pancreatic cancer patients.